AC Impedance Analysis of the Al/ZnO/p-Si/Al Schottky Diode: C-V Plots and Extraction of Parameters - M. Benhaliliba; Y.S. Ocak; H. Mokhtari; T. Kiliçoglu (Журнал нано- та електронної фізики)
In this research, we report on the measurement of the capacitance-voltage (C-V) characteristics Al / ZnO / p-Si / Al Schottky diode at room temperature and in dark condition fabricated by spray pyrolysis process. C-V characteristics, within the range of frequencies 5 kHz-5 MHz, are investigated and microelectronic parameters are extracted. Donor density and diffusion potential vary with frequency from 15 to 28 1014 cm – 3, 0.21 to 0.45 V. Besides, the interface state density of Al /ZnO /pSi/Al Schottky is determined and found to be 1012 (eV·cm²) – 1. Calculated at 1 MHz, the interfacial layer thickness and depletion layer width are of 760 Å and 0.28 μm.